2021
DOI: 10.3390/agriculture11050452
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nutritive Values through Comparison of Forage Yield and Silage Quality of Mono-Cropped and Intercropped Maize-Soybean Harvested at Two Maturity Stages

Abstract: Maize and soybean intercropping is a cereal-legume intercropping pattern that not only increases grain yield but also improves the nutritional value of silage. Experiments were conducted in the summer season to compare the yield and nutritional composition of the forage and silage quality of mono-cropped maize and intercropped maize-soybean harvested at two stages of maturity. The main treatments were one sole crop maize (SM) and four maize-soybean intercropping patterns (one-row maize to one-row soybean (1M1S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…Our results indicated that the mixed cropping of maize with legumes increased the CP of forage. Proper CP levels are essential in forages for many types of livestock that rely on them for nutrition [40]. The CFA and CA contents did not significantly differ (p > 0.05) among the maize-common bean mixture ratios, which were consistent with our results [40].…”
Section: Chemical Composition Of Foragessupporting
confidence: 88%
See 2 more Smart Citations
“…Our results indicated that the mixed cropping of maize with legumes increased the CP of forage. Proper CP levels are essential in forages for many types of livestock that rely on them for nutrition [40]. The CFA and CA contents did not significantly differ (p > 0.05) among the maize-common bean mixture ratios, which were consistent with our results [40].…”
Section: Chemical Composition Of Foragessupporting
confidence: 88%
“…The highest DMY (14.56 t ha −1 ) was found in sole maize (100:0 seeding ratio) compared with the other mixed forages in Figure 2B. This difference in DMY contents may be due to the effect of the harvesting stage of maturity [40]. Sole maize produced higher FFY and DMY than maize intercropped with soybean [40] and cowpea [41].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After each mowing, a 1 m × 1 m quadrat was selected from each plot to weigh the fresh grass yield, after which the fresh grass was brought back to the laboratory. The samples were air‐dried at 105°C to inactivate the enzymes (Soe Htet et al, 2021), subsequently dried at 65°C to a constant weight and weighed to calculate the dry‐to‐fresh ratio (dry grass weight/fresh grass weight × 100%). The average daily growth rate and stem‐to‐leaf ratio were determined using a previously described method (Wang et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…These results are in harmony with those obtained by Hassan et al (2017) who found that pearl millet gave the highest values of fresh and dry yields/fed followed by sudan grass and teosinte when they were grown either alone or intercropped with some legume crops. Also, many investigators found that fresh and dry forage yields/unit area of some grass forage crops were decreased when they were intercropped with some crops such as maize (Samarappuli and Berti, 2018), cowpea (Shahwan et al, 2013, Pal et al, 2014, Iqbal et al, 2017, Ginwal et al 2019and Qadir et al, 2021 and soybean (Salama andAbdel-Moneim, 2021 andSoe Htet et al, 2021).…”
Section: -2 Forage Productionmentioning
confidence: 99%